Kepemimpinan Pendidikan - Rohmat Rohmat (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Education institution represents the organization having unique character because in it there are learning process and activity of human empowerment. Logical consequence of education is arranging effectiveness of education organization that necessarily requires leadership. Effectiveness of education leadership will perform better if education leader have a number of ability. From function aspect, leader must able to carry out their function as manager, leader, and educator. The function requires a number of ability, which must be possessed by the leader to be able to run the organization effectively. Technical, interpersonal, and conceptual ability and moral condition represent the elementary aspect of education leader.